2018
DOI: 10.4102/sajpsychiatry.v24i0.1290
|View full text |Cite
|
Sign up to set email alerts
|

From victim to perpetrator to survivor: The psycho-social context of South African women offenders

Abstract: BackgroundThere is a paucity of research on women offenders in the South African context, particularly those referred for forensic psychiatric observation. Little is known about their life histories, the nature of their offences or the psycho-social contexts that enable, or are antecedents to, women’s criminal offending.AimThis research study, the largest of its kind in South Africa, examined the psycho-social contexts within which women offenders referred for psychiatric evaluation come to commit offences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, almost a third of the sample (35.4%) had an undocumented history of previous exposure to violence and abuse. Previous research has shown that exposure to violence predisposes to criminal behaviour, 2 , 10 , 18 thus it was important to determine the abuse history of all the women in the study; however, the incompleteness of the data has underestimated the frequency of domestic violence in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…For example, almost a third of the sample (35.4%) had an undocumented history of previous exposure to violence and abuse. Previous research has shown that exposure to violence predisposes to criminal behaviour, 2 , 10 , 18 thus it was important to determine the abuse history of all the women in the study; however, the incompleteness of the data has underestimated the frequency of domestic violence in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…25 Adverse childhood experiences are indeed linked to violent offending in both genders. However, violent offending particularly interpersonal violence in females has been linked to defensive reactions related to chronic past abuse, both in South Africa 26 and internationally. 27 A meta-analysis investigating the cycle of violence after exposure to childhood maltreatment among women, in the general and prison populations, found a significant, albeit small, positive association between ACEs and a wide array of violent behaviours.…”
Section: Adverse Childhood Experiences and Violent Offendingmentioning
confidence: 99%
“…Adverse childhood experiences are indeed linked to violent offending in both genders. However, violent offending particularly interpersonal violence in females has been linked to defensive reactions related to chronic past abuse, both in South Africa 26 and internationally. 27 …”
Section: Introductionmentioning
confidence: 99%